2023
DOI: 10.3390/nu15081927
|View full text |Cite
|
Sign up to set email alerts
|

n-3 PUFA Promotes Ferroptosis in PCOS GCs by Inhibiting YAP1 through Activation of the Hippo Pathway

Abstract: Polycystic ovary syndrome (PCOS) is an endocrine disorder characterized by hyperandrogenemia with multiple suspended sinus follicles, thickened cortical tissue, and excessive proliferation of ovarian granulosa cells that severely affects the fertility and quality of life of women. The addition of n-3 PUFA to the diet may slightly reduce body weight and greatly alleviate disturbed blood hormone levels in PCOS mice. We treated KGN as a cell model for n-3 PUFA addition and showed that n-3 PUFA inhibited the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The discovery that ferroptosis is inhibited in granulosa cells from patients with PCOS via the circRHBG-miR-515-5p-SLC7A11 axis emphasizes the importance of PCD other than apoptosis in this disease and may provide new diagnostic molecular markers or therapeutic targets [ 214 ]. A recent report described an experimental attempt to treat PCOS in a mouse model by inducing ferroptosis [ 324 ]. The administration of n-3 PUFAs in the diet to dehydroepiandrosterone-treated mice activated Hippo signaling and YAP1 exocytosis, and suppressed NRF2, a protein that regulates critical ferroptosis-related genes ( GPX4 , GSS , TFRC , HMOX1 , and others) [ 325 ], leading to the promotion of ferroptosis in ovarian granulosa cells.…”
Section: Pathologies Associated With Pcd Deregulation In the Ovarymentioning
confidence: 99%
“…The discovery that ferroptosis is inhibited in granulosa cells from patients with PCOS via the circRHBG-miR-515-5p-SLC7A11 axis emphasizes the importance of PCD other than apoptosis in this disease and may provide new diagnostic molecular markers or therapeutic targets [ 214 ]. A recent report described an experimental attempt to treat PCOS in a mouse model by inducing ferroptosis [ 324 ]. The administration of n-3 PUFAs in the diet to dehydroepiandrosterone-treated mice activated Hippo signaling and YAP1 exocytosis, and suppressed NRF2, a protein that regulates critical ferroptosis-related genes ( GPX4 , GSS , TFRC , HMOX1 , and others) [ 325 ], leading to the promotion of ferroptosis in ovarian granulosa cells.…”
Section: Pathologies Associated With Pcd Deregulation In the Ovarymentioning
confidence: 99%
“…recently found that n-3 polyunsaturated fatty acids (n-3 PUFAs) can activate the Hippo signaling pathway, inhibit yes-associated protein 1 (YAP1) from entering the nucleus, weaken the interaction between YAP1 and Nrf2, and increase the sensitivity of ovarian GC to ferroptosis. As a result, GC can alleviate follicular development arrest caused by abnormal proliferation of GC ( 51 ). In summary, oxidative stress, mitochondrial dysfunction, and abnormal secretion of nutritional factors associated with ferroptosis in GC affect the growth and development of ovaries.…”
Section: The Relationship Between Ferroptosis and Ovarian Diseasesmentioning
confidence: 99%